Physicochemical transformations of corn-based snacks with underexploited grains addition during storage: multi-analytical assessment - Rolandelli, Guido; Farroni, Abel Eduardo; Buera, María del Pilar (Wiley, 2022)
Corn-based snacks were prepared with the addition of 25% of millet, sorghum, quinoa, and canary seed ﬂours, which are scarcely used grains for human food and can grow in low-fertility soils. GuggenheimAnderson-de Boer (GAB) and D’arcy & Watt (GDW) sorption models provided information regarding water-solids interactions and microstructural arrangements. After storage for 2, 4, and 6 months, several physicochemical properties of snacks were measured and compared with freshly prepared products and raw blends. Addition of quinoa and canary seed ﬂours doubled phenolics content and antioxidant properties. Lipids oxidation kinetics was associated with water sorption, antioxidant properties, and carotenoids and phenolics stability. Starch gelatinisation and protein transformations were assessed through FTIR. Protein denaturation after thermal treatment reduced intermolecular associations with carotenoids and phenolic compounds, which enhanced their functionality as antioxidants. Addition of quinoa and canary seed ﬂours showed promising results for the development of innovative snacks with improved functional properties.